STRATEGI PEMASARAN PADA PT. INDOMARCO ADI PRIMA STOCK POINT GADING CEMPAKA NON PASAR (SP. GCNP) BENGKULU - Freddy Firmansyah Marpaung; Sulisti Afriani (UNIVED Press, 2016)
Freddy Firmansyah Marpaung, Sulisti Afriani; Method of data collection used method of questionnaire to distribute a list of questions to the respondent. Method of analysis used is SWOT that aims to identify factors internal factors (strengths and weaknesses) and external factors (opportunities and threats) are then inserted into the SWOT matrix. From the results it obtained a score of 9.7 for strength and 6.51 for the opportunities that indicate the quadrant position PT. Indomarco Adi Prima Stock Point Gading Cempaka Non Pasar (SP. GCNP) Bengkulu is in quadrant 1 or quadrant taking a turn aggressive strategy that is very favorable situation for PT. Indomarco Adi Prima Stock Point Gading Cempaka Non Pasar (SP. GCNP) Bengkulu because it has enormous power that can take advantage of existing opportunities.Key Words: Marketing Strategy, SWOT